Evaporation in nano/molecular materials - Davoodabadi, Ali; Ghasemi, Hadi (Advances in colloid and interface science, 2021)
Evaporation is a physical phenomenon with fundamental significance to both nature and technology ranging from plant transpiration to DNA engineering. Various analytical and empirical relationships have been proposed to characterize evaporation kinetics at macroscopic scales. However, theoretical models to describe the kinetics of evaporation from nano and sub-nanometer (molecular) confinements are absent. On the other hand, the fast advancements in technology concentrated on development of nano/molecular-scale devices demand appropriate models that can accurately predict physics of phase-change in these systems. A thorough understanding of the physics of evaporation in nano/molecular materials is, thus, of critical importance to develop the required models. This understanding is also crucial to explain the intriguing evaporation-related phenomena that only take place when the characteristic length of the system drops to several nanometers. Here, we comprehensively review the underlying physics of evaporation phenomenon and discuss the effects of nano/molecular confinement on evaporation. The role of liquid-wall interface-related phenomena including the effects of disjoining pressure and flow slippage on evaporation from nano/molecular confinements are discussed. Different driving forces that can induce evaporation in small confinements, such as heat transfer, pressure drop, cavitation and density fluctuations are elaborated. Hydrophobic confinement induced evaporation and its potential application for synthetic ion channels are discussed in detail. Evaporation of water as molecular clusters rather than isolated molecules is discussed. Despite the lack of experimental investigations on evaporation at nanoscale, there exist an extensive body of literature that have applied different simulation techniques to predict the phase change behavior of liquids in nanoconfinements. We infer that exploring the effect of electrostatic interactions and flow slippage to enhance evaporation from nanoconduits is an interesting topic for future endeavors. Further future studies could be devoted to developing nano/molecular channels with evaporation-based gating mechanism and utilization of 2D materials to tune energy barrier for evaporation leading to enhanced evaporation. [Display omitted] •Interfacial interactions could induce evaporation in nano/molecular geometries.•Flexible materials enhance evaporation of a confined liquid.•Cavitation is not common in nanomaterials due to the small size of the pores.•Solid-liquid interaction including steric and electrostatic forces determine the kinetic of evaporation.